2018
DOI: 10.1080/09593330.2018.1480063
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a small-scale wastewater treatment plant for removal of pathogenic protozoa (oo)cysts and indicator microorganisms

Abstract: The protozoa Giardia and Cryptosporidium are associated with numerous outbreaks of waterborne diseases worldwide. This study aimed to evaluate the concentration of Giardia spp. cysts, Cryptosporidium spp. oocysts, total coliforms, Escherichia coli and Clostridium perfringens in raw wastewater and their removals at UASB reactor, activated sludge system (operated conventionally and extended aeration) and slow sand filtration. Giardia spp. cysts were present in 100% and Cryptosporidium spp. oocysts in 31.4% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Also, 5 treatment systems out of 29 systems (17.24%), had 100% efficacy in removing worms and protozoa. While the results of recent studies have shown that about 82.75% of treatment plants had not 100% efficiency in removing worms and protozoa (14,29,43,44,51,53,(55)(56)(57)60,61,72). Overall, helminth infections, including parasitic eggs and larvae, are more easily removed by the treatment systems compared to the protozoans.…”
Section: Discussionmentioning
confidence: 99%
“…Also, 5 treatment systems out of 29 systems (17.24%), had 100% efficacy in removing worms and protozoa. While the results of recent studies have shown that about 82.75% of treatment plants had not 100% efficiency in removing worms and protozoa (14,29,43,44,51,53,(55)(56)(57)60,61,72). Overall, helminth infections, including parasitic eggs and larvae, are more easily removed by the treatment systems compared to the protozoans.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have reported that decentralized systems efficiently reduce pathogens, including bacteria (Salmonella and E. coli) [12], protozoans (Giardia spp.) [13], helminths (Ascaris lumbricoides) [14], hookworms (Strongyloides stercoralis) and trophozoites (Trichomonas and Enterobius vermicularis) [12]. Therefore, adequate wastewater treatment systems that produce safe treated wastewater for reuse and resources, whether centralized or decentralized, are crucial for further recovery, reuse and recycling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have reported that decentralized systems e ciently reduce pathogens, including bacteria (Salmonella and E. coli) [11], protozoans (Giardia spp.) [12], helminths (Ascaris lumbricoides) [13], hookworms (Strongyloides stercoralis) and trophozoites (Trichomonas and Enterobius vermicularis) [11]. Therefore, adequate wastewater treatment systems that produce safe treated wastewater for reuse and resources, whether centralized or decentralized, are crucial for further recovery, reuse and recycling.…”
Section: Introductionmentioning
confidence: 99%